2008
DOI: 10.1038/nn.2197
|View full text |Cite|
|
Sign up to set email alerts
|

Links from complex spikes to local plasticity and motor learning in the cerebellum of awake-behaving monkeys

Abstract: The hypothesis of cerebellar learning proposes that complex spikes in Purkinje cells engage mechanisms of plasticity in the cerebellar cortex; in turn, changes in the cerebellum depress the simple spike response of Purkinje cells to a given stimulus and cause the adaptive modification of a motor behavior. Although many elements of this hypothesis have been supported by prior experiments, the links between complex spikes, simple spike plasticity, and behavior have not yet been examined simultaneously during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
262
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(300 citation statements)
references
References 51 publications
(60 reference statements)
27
262
1
Order By: Relevance
“…In a variety of systems, CF activity has been shown to encode unexpected events and errors in movement, information appropriate for instructing circuit changes during motor learning (23)(24)(25)(26). Also consistent with a teaching role are the observations that direct electrical stimulation of IO/CFs can substitute for (27), that inhibition and lesion of the IO/CFs can prevent associative learning (28), and that lesions of the IO in trained animals result in extinction with continued paired training (29).…”
mentioning
confidence: 83%
“…In a variety of systems, CF activity has been shown to encode unexpected events and errors in movement, information appropriate for instructing circuit changes during motor learning (23)(24)(25)(26). Also consistent with a teaching role are the observations that direct electrical stimulation of IO/CFs can substitute for (27), that inhibition and lesion of the IO/CFs can prevent associative learning (28), and that lesions of the IO in trained animals result in extinction with continued paired training (29).…”
mentioning
confidence: 83%
“…Long-term associative plasticity in the flocculus in vitro: Temporal requirements matched to behavioral function Our finding that coincident parallel fiber and climbing fiber stimulation failed to induce LTD in the flocculus was surprising, given the multiple lines of evidence for a role of climbing fiber-triggered LTD in flocculus-dependent learning (e.g., Boyden et al, 2006;Hansel et al, 2006;Ito, 2001;Kimpo et al, 2014;Medina and Lisberger, 2008). However, in vivo, the activation of climbing fibers by performance errors would be delayed relative to the parallel fiber activity that caused the error, rather than coincident.…”
Section: Heterogeneity In the Rules For Long-term Plasticity At Cerebmentioning
confidence: 99%
“…During oculomotor learning, a spike in a climbing fiber on one trial is associated with a suppression of firing in its Purkinje cell target on the next trial (Kimpo et al, 2014;Medina and Lisberger, 2008;Lisberger, 2010, 2014). The temporal precision of this single-trial plasticity reported in vivo had appeared to be significantly less than what we found at the PF-to-PC synapses in vitro (hundreds of milliseconds vs. tens of milliseconds).…”
Section: During Associative Learning In Vivo Plasticity Of Floccularmentioning
confidence: 99%
“…Classical eyeblink conditioning, a simple form of cerebellar-dependent motor learning (De Zeeuw and Yeo, 2005;Lepora et al, 2009), is also accompanied by a learning-dependent decline in the frequency of simple spikes following the onset of predictive conditioned stimuli that generate conditioned responses (Jirenhed et al, 2007). Similarly, Medina and Lisberger (2008) investigated excitability changes in PCs in the monkey cerebellum during smooth pursuit eye movement adaptation, and also reported a progressive depression in simple spike activity and decreases in complex spike probability in PCs. Furthermore, the complex spikes on a given trial corresponded to a depression in simple spikes on the following trial.…”
Section: Cerebellar Cortical Physiology and Synaptic Plasticitymentioning
confidence: 99%
“…Kelly and Strick (2003) showed that the primary motor cortex, for example, interacts specifically with cerebellar lobules V, VI, VIIb, and VIIIa. These parts of the cerebellum are implicated in motor learning by specific electrophysiological signatures of plasticity, as revealed by trial-by-trial changes in the firing properties of PCs (Gilbert and Thach, 1977;Medina and Lisberger, 2008).…”
Section: Introductionmentioning
confidence: 99%